Altered lung structure and function in mid-childhood survivors of very preterm birth - Simpson, S.; Logie, K.; O'Dea, C.; Banton, G.; Murray, C.; Wilson, A.; Pillow, J.; Hall, Graham (BMJ Group, 2017)
Rationale Survivors of preterm birth are at risk of chronic and lifelong pulmonary disease. Follow-up data describing lung structure and function are scarce in children born preterm during the surfactant era. Objectives To obtain comprehensive data on lung structure and function in mid-childhood from survivors of preterm birth. We aimed to explore relationships between lung structure, lung function and respiratory morbidity as well as early life contributors to poorer childhood respiratory outcomes. Methods Lung function was tested at 9-11 years in children born at term (controls) and at =32 weeks gestation. Tests included spirometry, oscillatory mechanics, multiple breath nitrogen washout and diffusing capacity of the lung for carbon monoxide. Preterm children had CT of the chest and completed a respiratory symptoms questionnaire. Main results 58 controls and 163 preterm children (99 with bronchopulmonary dyspl asia) participated. Preterm children exhibited pulmonary obstruction and hyperinflation as well as abnormal peripheral lung mechanics compared with term controls. FEV1 was improved by 0.10 z-scores for every additional week of gestation (95% CI 0.028 to 0.182; p=0.008) and by 0.34 z-scores per z-score increase in birth weight (0.124 to 0.548; p=0.002). Structural lung changes were present in 92% of preterm children, with total CT score decreased by 0.64 (-0.99 to -0.29; p < 0.001) for each additional week of gestation. Obstruction was associated with increased subpleural opacities, bronchial wall thickening and hypoattenuated lung areas on inspiratory chest CT scans (p < 0.05). Conclusions Abnormal lung structure in mid-childhood resulting from preterm birth in the contemporary era has important functional consequences.